2013
DOI: 10.2106/jbjs.k.00607
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Malalignment Increases Risk of Failure After Total Knee Arthroplasty

Abstract: Patients with excessive preoperative alignment (>8° of varus or >11° of valgus) have a greater risk of failure (2.3%). Neutral postoperative alignment (2.5° through 7.4° of valgus) improves (1.9% for preoperatively deformed knees) but does not completely eliminate the risk of failure (0.5% for knees that were neutral both preoperatively and postoperatively). Careful attention should be paid to knee alignment during total knee arthroplasty, especially for patients with severe preoperative deformities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 1 publication
5
76
1
1
Order By: Relevance
“…However they found failure rates only increased if there was greater than 7.4°of valgus malalignment. This study demonstrated a relatively narrow range of alignment outcomes, well below the limits set by Ritter et al [32], which may in part be due to the single surgeon series, but failed to demonstrate any advantage in CATKR. Although the followup period was short we were unable to show any improvement in implant survival with CATKR compared to JATKR.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…However they found failure rates only increased if there was greater than 7.4°of valgus malalignment. This study demonstrated a relatively narrow range of alignment outcomes, well below the limits set by Ritter et al [32], which may in part be due to the single surgeon series, but failed to demonstrate any advantage in CATKR. Although the followup period was short we were unable to show any improvement in implant survival with CATKR compared to JATKR.…”
Section: Discussioncontrasting
confidence: 67%
“…Ritter et al [32] reviewed implant survival in relation to pre-operative and postoperative alignment and showed the importance of correct alignment in reducing the risk of implant failure. However they found failure rates only increased if there was greater than 7.4°of valgus malalignment.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive pre-operative malalignment predisposes to a greater risk of failure compared to well-aligned knees. For this reason it is important to correct the deformity during surgery even if it does not completely eliminate the increased risk of failure (1.9 vs 0.5 %) [3]. The valgus deformity is sustained by anatomical variations divided into bone tissue remodelling and soft tissue contraction/elongation.…”
Section: Introductionmentioning
confidence: 99%
“…Dr. Cross: The main advantage of using a neutrally aligned technique is the proven long-term success and survivorship when a neutral (or near neutral) mechanical axis is achieved. In a retrospective study of more than 5000 TKAs by Ritter et al [16], achieving a neutral mechanical alignment of ''anatomic'' valgus had a lower failure rate (0.74%) than patients outside the neutral mechanical axis (failure rate = 1.7%). However, the effect of achieving neutral mechanical alignment (0 ± 3°) has been recently called in to question.…”
Section: Dr Abdelmentioning
confidence: 96%
“…Regardless of the softtissue envelope, preoperative alignment, and age, a mechanically aligned TKA can always be performed. That said, large preoperative varus (> 8°) and valgus (> 11°) deformities have a higher failure rate [16]. Additionally, with an incompetent medial collateral ligament or lateral collateral ligament, additional constraint may be needed after the cuts are performed, despite achieving a neutral mechanical alignment.…”
Section: Dr Abdelmentioning
confidence: 99%